2001
DOI: 10.1046/j.1440-1746.2001.02612.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylglucosaminyltransferase V as a possible aid for the evaluation of tumor invasiveness in patients with hepatocellular carcinoma

Abstract: The present study demonstrated that there was a close association between tumor invasiveness and GnT-V activity in sera, and that the measurement of GnT-V may improve prognostic estimates and therapeutic outcomes for patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…One well characterized example is that of increased activity of N-acetylglucosaminyltransferase V, a key enzyme in the formation of branching asparagine-linked oligosaccharides that has been linked to tumor invasion and metastasis in multiple cancers (25)(26)(27)(28). An increase of ␤-1,6-branched oligosaccharides within metastatic lymph nodes of breast carcinomas has been reported, and the presence of the branched oligosaccharides was associated with poor prognosis (28).…”
Section: Altered Glycoproteins and Cancermentioning
confidence: 99%
“…One well characterized example is that of increased activity of N-acetylglucosaminyltransferase V, a key enzyme in the formation of branching asparagine-linked oligosaccharides that has been linked to tumor invasion and metastasis in multiple cancers (25)(26)(27)(28). An increase of ␤-1,6-branched oligosaccharides within metastatic lymph nodes of breast carcinomas has been reported, and the presence of the branched oligosaccharides was associated with poor prognosis (28).…”
Section: Altered Glycoproteins and Cancermentioning
confidence: 99%
“…Accumulated evidence indicates that alterations in N-linked glycosylation are a hallmark of various liver diseases, including hepatocellular carcinoma (5,8). For instance, expression of N-acetylglucosaminyltransferase-III and -V is increased in hepatocellular carcinoma (9,10). An N-glycan profiling study identified novel N-glycan structures in serum as prognostic markers of hepatocellular carcinoma (11).…”
Section: Introductionmentioning
confidence: 99%
“…nyltransferase-III and acetylglucosaminyltransferase-V in HCC were positively correlated with the malignant and metastatic potential of tumor cells (11)(12)(13). In addition, the ␣-1,6-fucosylation of ␣-fetoprotein provides a more accurate diagnosis of HCC from chronic liver disease and a good monitoring and prognosis marker for the early diagnosis of HCC (14).…”
mentioning
confidence: 97%